DYNAMIC DEVELOPMENT AND INITIATIVES TO ENHANCE THE POTENTIAL OF GREEN TOURISM IN THE REPUBLIC OF UZBEKISTAN - Akhmedkhodjaev, Ravshan (Educational Research in Universal Sciences, 2023)
This scientific article summarizes current initiatives, current trends, economic indicators, prospects for further dynamic development of the tourism industry, enhancing the potential of “green” tourism of New Uzbekistan.